Psychological aspects of motivation and job satisfaction of faculty members: the case of one state University in Kazakhstan - Almurzayeva, Bibigul; Summers, Danna; Davletkaliyeva, Yelizaveta (Przegląd Wschodnioeuropejski, 2019)
Psychological aspects of motivation and job satisfaction are integral parts of the effective and productive operations of any organization. In the context of higher education, it is one of the spheres, where satisfaction of faculty members, as well as appropriate motivational environment, has the paramount value for the effectiveness of a higher education institution and the quality of educational services. This research aims to explore the psychological aspects of motivation and job satisfaction of faculty members of one state university in Kazakhstan. Questionnaires concerning the job satisfaction level and motivation were distributed among 232 faculty members of one state university in Kazakhstan. The research findings show that the vast majority of participants have a relatively high level of job satisfaction, despite the existence of factors that negatively influence on the job satisfaction level, such as inappropriate work schedule, salary issues, and dealings with administration. At the same time, it becomes evident that favorable social and psychological climate, as well as relationships with colleagues can be considered as the most important components of psychological aspects of faculty members’ motivation. This study provides recommendations that can increase the job satisfaction level of faculty members and improve motivational environment in higher education institutions.